Theory of Electron Transport in Semiconductors A Pathway from Elementary Physics to Nonequilibrium Green Functions - Jacoboni, Carlo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book describes in details the theory of the electron transport in the materials and structures at the basis of modern micro- and nano-electronics. It leads and accompanies the reader, through a step-by-step derivation of all calculations, from the basic laws of classical and quantum physics up to the most modern theoretical techniques, such as nonequilibrium Green functions, to study transport properties of both semiconductor materials and modern low-dimensional and mesoscopic structures.
Basic concepts in semiconductor physics -- Survey of Classical Physics -- Fundamentals of Quantum Mechanics -- Fundamentals of Statistical Physics -- Crystal Structures -- Phonons -- Bloch States and Band Theory -- Effective-Mass Theorems, Envelope Function, and Semiclassical Dynamics -- Semiconductors -- Semiclassical transport in bulk semiconductors -- Electronic Interactions -- Boltzmann Equation -- Linear Transport -- Diffusion, Fluctuations, and Noise -- Nonlinear Transport -- Monte Carlo Simulation of Bulk Electron Transport -- Bulk Transport Properties of Main Semiconductors -- Quantum transport in bulk semiconductors -- Quantum Transport in Homogeneous Systems -- The Wigner-Function Approach to Quantum Transport -- Transport in semiconductor structures -- Inhomogeneous and Open Systems: Electronic Devices -- Low-Dimensional Structures -- Carbon Nanotubes -- Coherent Transport in Mesoscopic Structures -- Semiconductor Photo Gallery -- Quantum transport with non-equilibrium Green functions -- Second-Quantization Formalism -- to Green Functions -- Wick–Matsubara Theorems -- Perturbation Expansion of Green Functions: Feynman Diagrams and Dyson Equation -- Nonequilibrium Green Functions Applied to Transport: Quantum Boltzmann Equation -- NonEquilibrium Green Functions Applied to Transport: Mesoscopic Systems -- Appendices -- Vector Spaces and Fourier Analysis -- One-Dimensional Potential Step, Barrier, and Well -- Quantum Theory of Harmonic Oscillator -- Landau Levels -- Perturbation Theory.
Keywords: Condensed matter; Nanotechnology; Engineering; Condensed Matter Physics; Nanotechnology; Engineering, general